A rechargeable aqueous Zn2+-battery with high power density and a long cycle-life. Issue 11 (11th October 2018) - Wang, Fei; Hu, Enyuan; Sun, Wei; Gao, Tao; Ji, Xiao; Fan, Xiulin; Han, Fudong; Yang, Xiao-Qing; Xu, Kang; Wang, Chunsheng
Abstract : The bivalence of Zn 2+ was delocalized by multiple atoms through the p–d hybridization, rendering its high mobility. Abstract : Li-Ion batteries (LIBs) are approaching their energy limits imposed by their intercalation chemistry nature. As alternatives, multivalent (MV) chemistries bring both promises and challenges, with the main obstacle being the sluggish diffusion of MV-cations due to their strong electrostatic interaction with host lattices. In this work, we demonstrated that polyanion based robust crystal architecture could enable ultrafast and reversible Zn 2+ -intercalation and de-intercalation at a high working voltage. The nominal bivalence of Zn 2+ was successfully delocalized by multiple atoms through the p–d hybridization between the V-d and O-p orbitals; hence the inserted Zn 2+ only bears an effective charge of 1.336, rendering its high mobility. The novel aqueous rechargeable 1.7 V Zn/LiV2 (PO4 )3 cell based on such a mechanism delivers a high power density (8000 W kg −1 at 60C) comparable to supercapacitors, and a high energy density (218 W h kg −1 at 1C) close to LIBs, with an extraordinarily long cycle life of 4000 cycles. All of these parameters far exceed those of Zn batteries reported so far. The cell-level volumetric and specific energy densities of the Zn/LiV2 (PO4 )3 cell are 320 W h L −1 and 150 W h kg −1, respectively, which are even better than those of first-generation LIBs. Combined with the intrinsic safety of its aqueous chemistry and its wide working temperature range, this cell makes a strong candidate for automotive applications.